2018
DOI: 10.1002/pc.24820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of defined amount of voids on the mechanical properties of carbon fiber‐reinforced plastics

Abstract: The fault‐free fabrication of fiber‐reinforced plastics (FRPs) is a big hurdle for textile and composite manufacturers. Voids are generated during the infiltration process of FRPs, which then reduce the mechanical performance of FRPs. This paper describes the effect of defined amount of voids on the mechanical properties, such as tensile, bending, impact and inter‐laminar shear strength of FRPs. The defined amount of voids in carbon FRPs are produced by a newly developed process—mixing of a foaming agent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, Esnaola et al [ 69 ] found that the fibre volume fraction of glass fibre-reinforced epoxy has no significant effect on the ILSS as determined by the short beam shear test. Nevertheless, a higher void content in the vacuum infusion samples is expected to have a negative effect on the ILSS due to the reduction in the sliding resistance between individual fibre layers by an increasing void content [ 70 ]. For the results presented here, it is assumed that the epoxy resin used in vacuum infusion leads to better fibre/matrix adhesion than the bio-based epoxy resin used in the autoclave injection process.…”
Section: Resultsmentioning
confidence: 99%
“…However, Esnaola et al [ 69 ] found that the fibre volume fraction of glass fibre-reinforced epoxy has no significant effect on the ILSS as determined by the short beam shear test. Nevertheless, a higher void content in the vacuum infusion samples is expected to have a negative effect on the ILSS due to the reduction in the sliding resistance between individual fibre layers by an increasing void content [ 70 ]. For the results presented here, it is assumed that the epoxy resin used in vacuum infusion leads to better fibre/matrix adhesion than the bio-based epoxy resin used in the autoclave injection process.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent years, the fabrication of defined local defects inserted FRPs has received considerable attention from the composite community [12][13][14][15][16][17][18][19][20][21][22]. In [12][13][14], defined local defect inserted FRPs were fabricated by blind holes of varying diameters in different layers of FRPs and defined local defects of polytetrafluorethylene (PTFE).…”
Section: Introductionmentioning
confidence: 99%
“…In-depth knowledge of dynamic material behavior should enable more efficient use of materials while simultaneously preserving the structural integrity of a component under dynamic load. Although there are numerous research activities focused on novel testing methods for textiles as well as for requirement-adapted reinforcing structures in the field of FRP [6][7][8][9][10][11][12][13][14][15], current insight into fiber properties is mainly based on research results according to Wang et al [16,17].…”
Section: Introductionmentioning
confidence: 99%